Factors influencing investments into human resources to support company performance - Jarmila Šebestová; Cristina Raluca Popescu (Journal of Risk and Financial Management, 2022)
Human resources are very important in a business; however, the return on investment in human resources is longer than in fixed assets, so entrepreneurs frequently consider how much to actually invest. This article, based on primary research, examines the motivations for investment when a 20% profit is typically invested with a model return of around 14%. Those findings are supported by the results presented in Archetype models based on similarity clustering. The results are based on an empirical study (278 respondents, omnibus survey) in the Czech Republic. Moreover, the study concludes that the business experience positively influences human resource management and future development to increase the investment share. In essence, this article displays the paramount importance of human resources and human resource management in the international business environment, demonstrating that investments in human resources are crucial to the success of all businesses, positively and consistently supporting organizations' performance, and entrepreneurship will continue to remain a vital component of the activities belonging to the post COVID-19 era. In addition, in an era governed by the influences specific to the knowledge-based society and the knowledge-based economy, in which intellectual capital will be considered one of the most relevant intangible assets of entities all over the world, the measurement of human resources investment will turn out to be essential for the success of all businesses, while taking the necessary steps in supporting sustainability, sustainability assessment and Sustainable Development Goals (SDGs).
Keywords: 330; human resources; investments; motivation; archetypes; performance; intellectual capital